2018
DOI: 10.1002/cam4.1672
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiles of tumor contrast enhancement: A radiogenomic analysis in anaplastic gliomas

Abstract: The presence of contrast enhancement (CE) on magnetic resonance (MR) imaging is conventionally regarded as an indicator for tumor malignancy. However, the biological behaviors and molecular mechanism of enhanced tumor are not well illustrated. The aim of this study was to investigate the molecular profiles associated with anaplastic gliomas (AGs) presenting CE on postcontrast T1‐weighted MR imaging. In this retrospective database study, RNA sequencing and MR imaging data of 91 AGs from the Cancer Genome Atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Since certain mesenchymal components in the growth process of xenografts were derived from NOD-SCID nude mice (34,35), the expression levels of immune-associated genes were decreased in the xenografts. The contrast enhancement and increased K trans value indicated that the original tumors exhibited significant angiogenic activity and high vascular permeability (36), which may be attributed to the increased expression levels of the angiogenesis-associated genes in the original tumors (37)(38)(39). The rADC values of the original tumors were significantly lower compared with the xenografts, which may be attributed with the higher expression levels of the cell adhesion and extracellular matrix-associated genes noted in the original tumors, which in turn resulted in a higher cell density (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Since certain mesenchymal components in the growth process of xenografts were derived from NOD-SCID nude mice (34,35), the expression levels of immune-associated genes were decreased in the xenografts. The contrast enhancement and increased K trans value indicated that the original tumors exhibited significant angiogenic activity and high vascular permeability (36), which may be attributed to the increased expression levels of the angiogenesis-associated genes in the original tumors (37)(38)(39). The rADC values of the original tumors were significantly lower compared with the xenografts, which may be attributed with the higher expression levels of the cell adhesion and extracellular matrix-associated genes noted in the original tumors, which in turn resulted in a higher cell density (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…2), texture feature associations did not demonstrate similar consistency. For example, measures of heterogeneity (GLCM information measure of correlation 1, GLRLM run length nonuniformity, GLSZM gray level nonuniformity) associated negatively with expression of immune gene signatures in head and neck cancer [73], whereas the opposite association appeared to be true of breast cancer and glioma [53,62] (Fig. 3).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…1), we identified 54 studies in which imaging features were associated with tumor immune phenotypes (Table 1 and Supplemental Table 1) or response to immunotherapy (Table 2 and Supplemental Table 2). The following types of cancers were investigated: lung [3,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] (20), brain [45][46][47][48][49][50][51][52][53][54] (10), breast [55][56][57][58][59][60][61][62][63] (9), liver [9,41,[64][65]…”
Section: Overview Of Radiogenomic Studies On Tumor Immune Biology and Immunotherapy Responsementioning
confidence: 99%
“…By far the most common theme in computational glioma survival prediction involving imaging relates to glioma tumor grading. Numerous publications have employed tumor grading from imaging features as a starting point to help develop prognostic biomarkers (21,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Some publications have focused strictly on glioma grading (31,50,58) and T2FLAIR (T2 fluid-attenuated inversion recovery) images, and the risk factors and OS were explored by Kaplan-Meier survival analysis by stratifying patients into low-and high-risk groups (C-Index 0.707 and 0.711 in training and test cohorts respectively) (31).…”
Section: Imaging and Tumor Grading-based Survival Predictionmentioning
confidence: 99%